Publication Speed, Reporting Metrics, and Citation Impact of Cardiovascular Trials Supported by the National Heart, Lung, and Blood Institute. Issue 8 (31st July 2015) - Gordon, David; Cooper‐Arnold, Katharine; Lauer, Michael
Abstract : Background: We previously demonstrated that cardiovascular (CV) trials funded by the National Heart, Lung, and Blood Institute (NHLBI) were more likely to be published in a timely manner and receive high raw citation counts if they focused on clinical endpoints. We did not examine the metrics of trial reports, and our citation measures were limited by failure to account for topic‐related citation behaviors. Methods and Results: Of 244 CV trials completed between 2000 and 2011, we identified 184 whose main results were published by August 20, 2014. One investigator who was blinded to rapidity of publication and citation data read each publication and characterized it according to modified Delphi criteria. There were 46 trials (25%) that had Delphi scores of 8 or 9 (of a possible 9); these trials published faster (median time from trial completion to publication, 12.6 [interquartile range IQR, 6.7 to 23.3] vs. 21.8 [IQR, 12.1 to 34.9] months; P <0.01). They also had better normalized citation impact (median citation percentile for topic and date of publication, with 0 best and 100 worst, 1.92 [IQR, 0.64 to 7.83] vs. 8.41 [IQR, 1.80 to 24.75]; P =0.002). By random forest regression, we found that the 3 most important predictors of normalized citation percentile values were total costs, intention‐to‐treat analyses (as a modified Delphi quality measure), and focus on clinical (not surrogate) endpoints. Conclusions: NHLBI CV trials were more likely to publish results quickly and yield higher topic‐normalized citation impact if they reported results according to well‐defined metrics, along with focus on clinical endpoints.